Calcium influx and activation of Calpain I mediate acute reactive gliosis in injured spinal cord - Du, S; Rubin, A; Klepper, S; Barrett, C; Kim, YC; Rhim, HW; Lee, EB; Park, CW; Markelonis, GJ; Oh, TH (ACADEMIC PRESS INC, 1999)
Buffering extracellular pH at the site of a spinal cord crush-injury may stimulate axonal regeneration in rats (1; Guth et al., Exp. Neurol. 88: 44-55, 1985). We demonstrated in cultured astrocytes that acidic pH initiates a rapid increase in immunoreactivity for GFAP (GFAP-IR), a hallmark of reactive gliosis (2; Oh ct al., Glia 13: 319-322, 1995). We extended these studies by investigating the effects of certain treatments on reactive gliosis developing in situ in a rat spinal cord injury model. A significant reactive gliosis was observed within 2 days of cord lesion in untreated crush or vehicle-treated, crush control animals as evidenced by increased GFAP-IR and hypertrophy of astrocytes. By contrast, infusion of Pipes buffer (pH 7.4) into the lesion site significantly reduced this increase. The increased GFAP-IR appeared to be linked to Ca2+ influx since infusion of a blocker of L-type calcium channels, nifedipine, reduced the ensuing reactive gliosis significantly. While Ca2+ modulates many signaling pathways within cells, its effect on reactive gliosis appeared to result from an activation of calpain I. Calpain inhibitor I, a selective inhibitor of mu-calpain, also significantly reduced reactive gliosis. However, calpain inhibitor II, a close structural analog which blocks m-calpain, had no salutary effect. We suggest, therefore, that the initial reactive gliosis seen in vivo may result from the activation of a neutral, Ca(2+-)dependent protease, calpain I, through calcium influx. (C) 1999 Academic Press.
Keywords: FIBRILLARY ACIDIC PROTEIN; PERMEANT CA2+ CHELATORS; CEREBRAL BLOOD-FLOW; INTERMEDIATE FILAMENTS; NERVOUS-SYSTEM; BRAIN INJURY; RAT-BRAIN; ASTROCYTES; MECHANISMS; GLUTAMATE